2021
DOI: 10.1002/adfm.202110997
|View full text |Cite
|
Sign up to set email alerts
|

Reprogrammable Soft Robot Actuation by Synergistic Magnetic and Light Fields

Abstract: Soft robots controlled by different actuation schemes are flourishing owing to the continued development of smart materials. However, most of the existing actuators are powered by a single source with predetermined mechanical properties and motion characteristics. Speed, power, and efficiency of these actuators are thus far inferior to their conventional counter parts. How to preload or alter the internal energy distribution and trigger rapid kinetic energy release combined with re-programmability is a challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Figure 3b shows a series of images for one oscillation cycle of the PP/CB actuator (9 mm × 3 mm × 100 μm) at different times with a light intensity of 800 mW cm −2 during stable oscillation. The actuator completed one oscillation cycle in 0.3 s, with maximum bending curvature of 7.3 cm −1 and displacement of 15.7 mm, with the vertical line as the oscillation center, and exhibited 0.9% light-to-work energy conversion efficiency (Supplementary Note 1 ), which was superior to that of reported light-responsive actuators, including polycarbonate/carbon nanotube (CNT) (0.01%) 60 , CNT/polydimethylsiloxane (PDMS) (0.58%) 39 , and Fe 3 O 4 NPs@graphene oxide (GO) (0.38%) 61 . The corresponding infrared images during one oscillation cycle showed that the minimum temperature during actuation (42.7 °C) occurred at almost the maximum bending curvature (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Figure 3b shows a series of images for one oscillation cycle of the PP/CB actuator (9 mm × 3 mm × 100 μm) at different times with a light intensity of 800 mW cm −2 during stable oscillation. The actuator completed one oscillation cycle in 0.3 s, with maximum bending curvature of 7.3 cm −1 and displacement of 15.7 mm, with the vertical line as the oscillation center, and exhibited 0.9% light-to-work energy conversion efficiency (Supplementary Note 1 ), which was superior to that of reported light-responsive actuators, including polycarbonate/carbon nanotube (CNT) (0.01%) 60 , CNT/polydimethylsiloxane (PDMS) (0.58%) 39 , and Fe 3 O 4 NPs@graphene oxide (GO) (0.38%) 61 . The corresponding infrared images during one oscillation cycle showed that the minimum temperature during actuation (42.7 °C) occurred at almost the maximum bending curvature (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 92%
“…An object was first entangled within the spiral-shape actuator under AMF. Apart from magneto-thermal responsiveness, M-PULCEs also can be manipulated by permanent magnets because of the superparamagnetic property of the added Fe 3 O 4 NPs ( 50 ). Under the guidance of the permanent magnet, the M-PULCE actuator with the “cargo” rolled forward and passed into the opaque tube.…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, the different microrobots are interconvertible by reversibly disassembling and reassembling the composed modules, making the modularly assembled microrobots completely reconfigurable and recyclable. Such reconfigurability and recyclability of the microrobots endowed by the modular assembling technique are unique to existing soft robotics manufactured by any other techniques, ,,,,,,,,,,,,,, where the actuated deformation and locomotion mode are usually determined permanently or require sophisticated processing steps to reconfigure by locally reprogramming the material properties. With these combined advantages of multimodal locomotion, small scale, detachability and reassemblability, and easy controllability, the modularly assembled microrobots are expected to usher in a broad prospect for unlimited design and mass-manufacture of diverse soft robots with the capability of executing complicated tasks in multiple and extreme environments.…”
Section: Discussionmentioning
confidence: 99%
“…Of the different actuation strategies for the miniature soft robots, the use of a magnetic field has been one of the most common due to its combined advantages of untethered and spatiotemporal control, rapid response, low cost, and relative biosafety. To enable magnetism to steer the motion and locomotion of the soft robots, the most popular fabrication technique is to blend micro- or nanoscale magnetic media (usually particles or wires) into soft polymer matrices (e.g., elastomers and gels) and then shape and solidify the composites together. ,,,, ,,,,, , During the blending process, the spatial distribution/orientation and magnetization profile of the media are controlled and programmed inside the matrix to facilitate the generation of desired actuation force/torque upon applying external magnetic field. In this way, the obtained magnetic soft robots can only achieve a limited range of locomotion modes and the overall dexterity is restricted due to the permanently determined material properties (e.g., the magnetization profiles) once programmed and solidified. ,, There have been a few efforts to achieve reprogrammable actuation for the soft robots, such efforts, however, are usually accompanied with multiple processing and/or actuating steps (e.g., heating magnetic materials above the Curie temperature and then reorienting the magnetic domains during cooling ,, ) and cannot be extended to a more general material system. Besides, existing manufacturing techniques for the magnetic soft robots, such as multimaterial 3D/4D printing, ,,,, soft lithography, ,,,,, and mold casting, ,,,,,, usually apply to a relatively large scale (millimeters and above).…”
Section: Introductionmentioning
confidence: 99%